Evidence for a Relatively Warm Mid‐to Late Holocene on the Southeastern Tibetan Plateau. Issue 15 (12th August 2022) - Feng, Xiaoping; Zhao, Cheng; D'Andrea, William J.; Hou, Juzhi; Yang, Xiangdong; Xiao, Xiayun; Shen, Ji; Duan, Yanwu; Chen, Fahu
Abstract: The Holocene temperature discrepancy between paleoclimate reconstructions and climate model simulations—known as the Holocene temperature conundrum—calls for new high‐quality Holocene temperature records at high elevations. Here, we present a quantitative Holocene mean annual air temperature record based on a site‐specific branched glycerol dialkyl glycerol tetraethers calibration from a small remote alpine lake on the southeastern Tibetan Plateau. The record reveals a temperature history comprising a relatively cool early Holocene (before 7 ka) followed by a warmer mid‐ to late‐Holocene (after 7 ka), which was likely linked to increasing local annual insolation and greenhouse gases. Three cold events punctuated the general warming trend ca. 10.4 ka, 3.7 ka, and 1.7 ka BP, and correspond closely in time to ice rafting events in the North Atlantic, and to episodes of volcanism and/or unusual solar activity. The entire Holocene temperatures are cooler than the previously identified anthropogenic warming from 1990–2015 AD. Plain Language Summary: The scarcity of high‐quality, quantitative Holocene temperature records from terrestrial archives, especially at high elevations, such as the Tibetan Plateau, limits our understanding of the temperature history of the Holocene. Here, we present a molecular fossil‐based mean annual air temperature record for the last 12, 000 years from sediments preserved in a small remote alpine lake. The new record shows that the early Holocene was relatively cool and was followed by a warmer mid‐ to late‐ Holocene, which is consistent with results from climate modeling studies. This Holocene warming trend was probably due to increases in regional annual solar radiation and additional radiative forcing of greenhouse gases. The reconstruction captures the anthropogenic warming of the past 25 years (1990–2015 AD) and shows it to be unusual during the past 12, 000 years. Key Points: An unreported cooler early Holocene (before 7 ka BP) temperature record was presented at high elevations on the southeastern Tibetan Plateau The entire Holocene mean annual temperatures are cooler than the previously identified anthropogenic warming at this site from 1990 to 2015 AD Three multi‐centennial cold events centered on 10.4, 3.7, and 1.7 ka BP are observed in the record